MODL-02. A novelCre-conditionalcMYC-driven MB Group 3 transgenic mouse model shows traceable leptomeningeal dissemination. (3rd June 2022) - Morcavallo, Alaide; Barker, Karen; Kwok, Colin; Boult, Jessica K R; da Silva, Patricia Benites Goncalves; Okonechnikov, Konstantin; Zuckermann, Marc; Gorrini, Chiara; Jacques, Thomas S; Robinson, Simon P; Clifford, Steven C; Weiss, William A; et al.
Abstract: Medulloblastoma (MB), the most common embryonal tumour of the Central Nervous System, occurs in the cerebellum. Treatment regimens involve surgery, craniospinal radiotherapy, and chemotherapy. The greatest mortality is associated with disseminated disease, almost exclusively found in the leptomeningeal space. Unfortunately, knowledge about the aetiology of MB spread is limited and the need for kinder and efficacious therapy remains an unmet goal. Of the four molecular classified MB groups, Group3 (Gr3) MB presents with a high frequency of metastasis at diagnosis, with the worst overall survival. Gr3 MB tumours are dominated by primitive progenitor-like cells and cMYC deregulation; often, p53 deficiency is observed at relapse. To dissect the biology of primary and metastatic Gr3 MB, we have developed a new germline genetically engineered mouse model (GEMM), harbouring cMYC amplification in a Tamoxifen-inducible p53 functional background ( Trp53ERTAM strain). A novel LSL- cMYC-CopGFP-Luciferase transgene was integrated into the Rosa-26 locus of the mouse genome. Transgenic mice were crossed with a strain expressing Cre recombinase under the Blbp promoter targeting embryonic neural progenitors, and subsequently bred to Trp53ERTAM mice. As result, the cMYC overexpression was sufficient to generate tumours. Tumour penetrance was observed in all the expected tumour bearing genotypes, with increased aggressiveness in a non-functional p53 background. Bioluminescence imaging demonstrated tumour onset in the brain and dissemination along the spinal cord. CopGFP positive tumour cells were isolated from primary and metastatic tumours. Pathological interrogation confirmed that tumours present large cell/anaplastic (LCA) histology. Analysis of preliminary transcriptional profiling data proved that tumours cluster with human Gr3 MB. Ongoing methylation profiling and multi-omics approaches will inform on the tumour cells of origin and clonal divergence of primary tumour versus metastasis. In conclusion, we have successfully developed a novel immunocompetent mouse model of metastatic Gr3 MB with which we can investigate therapeutic vulnerabilities of MB.